ANALISIS PENGARUH REAGEN MAX GOLD DAN GRINDING TIME TERHADAP RECOVERY Au - Roby Maryudi; Amirin Kusmiran; Rita Desiasni (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2020)
PT XX is one of the largest copper companies in the world. There are 2 main minerals spread in PT XX, namely copper (Cu) and Gold (Au). With a processing capacity of 120,000 tons per day, PT XX is able to produce around 2000 tons of concentrate per day. There are several problems in processing, including decreasing the acquisition of grade and recovery of copper and gold because the gold content is still covered in impurities. The sample used is derived from cleaner, namely Polishing mill produck. This study aims to see the effect of grinding time on Au recovery and grade concentrate and see the effect of Max Gold and Pax reagents on recovery of Au and Au grade. The method used is grinding and flotation. The grinding process varies 0, 5 and 10 minutes and flotation using reagents and max gold, based on the results of the study it was found that the smaller the particle size with 10 minutes grinding using the pax reagent the grade and recovery gain increased for grade 6.62 ppm and recovery 84.7%.